THE COMPETENCY-BASED CURRICULUM DEVELOPMENT IN THE INDEPENDENT CURRICULUM AT INDONESIAN UNIVERSITIES - Muhammad Iqbal Ismail; Latif; Denies Susanto (Prosiding Amal Insani Foundation, 2026)
Competency-based curriculum development is a strategic approach to improving the quality of education in Indonesia, especially in addressing the challenges of the Fourth Industrial Revolution and globalization. The implementation of the Merdeka Curriculum, introduced by the Ministry of Education, Culture, Research, and Technology of Indonesia, aims to provide greater autonomy to educational institutions in designing flexible curricula that meet the needs of the workforce. This study employs a descriptive qualitative approach with a literature review technique to collect and analyze relevant data. Literature searches were conducted via Google Scholar using relevant keywords, restricting results to articles published between 2020 and 2023. Literature analysis indicates that the development of competency-based curricula aligned with the Indonesian National Qualifications Framework (KKNI) and the integration of technology in teaching, such as augmented reality and digital media, can enhance graduate competencies and learning effectiveness. Additionally, collaboration between higher education institutions and industries, as well as the development of entrepreneurship programs on campus, significantly contributes to students' job readiness. This research provides practical and strategic recommendations for more effective and relevant curriculum development, supporting the improvement of higher education quality in Indonesia and producing competent and innovative graduates.